Influence of Husbands’ Knowledge and Support on Anxiety Among Menopausal Women: A Literature-Based Analysis - Tri Ardayani Yani (Journal of health research and technology, 2026)
Menopause marks the end of a woman’s reproductive phase, characterized by declining levels of estrogen and progesterone and the cessation of ovarian function. This study employed a literature review to examine attitudes, readiness, and psychological experiences of menopausal women. A systematic search was conducted using the keywords “attitude,” “readiness,” and “menopausal women” across Google Scholar and PubMed. Inclusion criteria required articles to be original, published between 2021 and 2025, written in English or Indonesian, and fully accessible; partially available publications were excluded. The search identified 40 studies, of which 30 met initial screening criteria. Nineteen articles were included in the final review, alongside 25 national publications. Findings indicate that women’s anxiety during menopause is strongly influenced by their husbands’ knowledge and level of support, highlighting the importance of spousal involvement in managing menopausal well-being.